Konstruksi dan reproduksi kebudayaan - Abdullah, Irwan (Yogyakarta: Pustaka Pelajar, 2006)
Collection of articles on various socio-cultural aspects with reference to Indonesia; anthropological perspectives
Daftar pustaka: p. 259-270
Keywords: Indonesia -- Civilization; Indonesia -- Social life and customs; Indonesia -- Cultural policy